2008
DOI: 10.1038/jhh.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour ambulatory blood pressure for the management of antihypertensive treatment: a randomized controlled trial

Abstract: The aim of this study was to assess whether the use of 24-h blood pressure (BP) measurement in the management of antihypertensive therapy improves BP in patients with sustained hypertension. Patients with sustained hypertension (office BP X140/90 mm Hg, and 24-h systolic BP X130/80 mm Hg) were randomly assigned to a strategy using 24-h BP to manage antihypertensive treatment (target o130/80 mm Hg) or to a standard strategy using office BP (target o140/90 mm Hg). The primary end point was change in 24-h systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
6
0
2
Order By: Relevance
“…Our finding that BP decreased between T0 and T1 is in line with other studies which showed that the implementation of ABPM contributed to a more effective antihypertensive treatment [52-54]. However, it is necessary to take into consideration that at T0 the mean 24h BP values of the whole sample only marginally exceeded the recommended ABPM thresholds.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that BP decreased between T0 and T1 is in line with other studies which showed that the implementation of ABPM contributed to a more effective antihypertensive treatment [52-54]. However, it is necessary to take into consideration that at T0 the mean 24h BP values of the whole sample only marginally exceeded the recommended ABPM thresholds.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, ABPM has been shown to be a better predictor of cardiovascular complications and death than CBPM 3,4 and may help to implement a more efficient BP-lowering treatment regimen. 5,6 ABPM values are usually considered to be lower than conventional BP (CBP) values in the same individual. Accordingly, diagnostic thresholds for hypertension based on 24-hour ABPM are lower than those for CBPM.…”
Section: Hypertensionmentioning
confidence: 99%
“…Tal como o observado para a AMPA, a generalidade dos estudos originais referentes à utilização da MAPA reportam taxas mais elevadas de controlo tensional, entre 24% a 57% (Quadro VIII). [42][43][44][45] Os estudos foram aplicados no contexto do seguimento de hipertensos tratados em cuidados de saúde primários, na Suiça, 42 Espanha (de larga escala), 43 Reino Unido 44 e Itália. 45 Nestes estudos, para cada hipertenso, a MAPA revelou, em média, valores mais baixos do que a PA medida pela técnica do consultório e, por inerência, maiores taxas de controlo.…”
Section: Estudos Originaisunclassified
“…No entanto, na maioria dos estudos realizados em contexto de cuidados de saúde primários, um dos quais realizado na população portuguesa, 39 a hipertensão da bata branca tem maior peso. Os estudos suiço 42 e britânico 44 foram considerados com nível de evidência 2 pelo inferior poder estatístico inerente a amostras mais reduzidas, e por falhas na caracterização inicial da população. Os dois restantes estudos foram considerados bons sob o ponto de vista metodológico (nível de evidência 1).…”
Section: Estudos Originaisunclassified